L’utilisation d’adhésifs optiques réticulables aux UV pour le collage d’objets d’art en verre transparent coloré, à surface d’encollage réduite - Viviane Bechoux (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This research focuses on two issues : 1° The possibility to use UV-crosslinkable adhesives to bond transparent coloured glass.2° The glass bonding is very complex when the parts to be joined are thin, fragile, and when the bonding surface is reduced to a few millimetres in size. In this case, the mechanical strength of the bonding and the speed of the curing process of the adhesive are the first criteria to be taken into account to ensure a reliable final bonding.